The use of fentanyl in pain management in head and neck cancer patients: a narrative review. Issue 3 (August 2018) - Giusti, Raffaele; Bossi, Paolo; Mazzotta, Marco; Filetti, Marco; Iacono, Daniela; Marchetti, Paolo
Background: Head and neck (H&N) cancers account for about 5% of all malignant tumours. Pain is one of the most feared consequences of H&N neoplasms and is experienced by up to 80% of patients and worsens their quality of life inhibiting speaking, eating, drinking or swallowing. Nevertheless, pain is still often underestimated and undertreated. Objectives: The role of opioids in cancer pain has been well established but evidences about the role and the relative effectiveness of opioids such as fentanyl in the context of H&N cancer pain remains unclear. Methods: A literature review based on the guidance of the Centre for Reviews and Dissemination was conducted. An iterative approach was used starting with an electronic search in the MEDLINE database. The search terms (('Neoplasms'[Mesh]) AND 'Head and Neck Neoplasms'[Mesh]) AND 'Fentanyl'[Mesh] were used. Results: A total of 18 publications were found by the first performed search on PubMed. Other publications concordant with our aim were found by cross-reference. Considering inclusion and exclusion criteria for our review, eight papers resulted eligible for analysis. Conclusion: Fentanyl transdermal therapeutic system (TTS) seems to be an important option, thanks to the way of administration, the good safety and tolerability profiles to control baseline pain. For breakthrough cancer pain (BTcP), several formulations of transmucosal fentanyl are available. All the formulations seem to be active and safety but we lack head-to-head studies of fentanyl versus other strong opioids, as well as with different formulation of fentanyl, particularly for BTcP where H&N cancer population is very poorly represented.